Developing English Vocabulary Through Wordwall - Julia Rokhiatul Misikiyah Lia; Laras Putriani; Wisnu Arya Padma; Cici Situmorang (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Vocabulary mastery is an essential component in learning English because it is the foundation for the development of various language skills. However, students still face obstacles in learning English vocabulary due to the lack of interactive English learning. This research aims to describe students' experiences, responses, and motivations in developing English vocabulary, especially adjectives, through the use of wordwall media. This research uses a qualitative descriptive approach by involving students of the English language education study program at Institut Prima Bangsa Cirebon as participants. Data collection was carried out through semi-structured interviews after students participated in adjective vocabulary learning using Wordwall, then the data was analyzed narratively. The results of the study show that Wordwall helps students in understanding the form of adjectives, both from the aspects of spelling and pronunciation, through exercises that are carried out repeatedly. Students also show an increase in the ability to use adjectives in simple sentences as well as an increase in confidence, especially in writing skills. In addition, the use of Wordwall has been proven to increase student motivation to learn because the learning process is more interesting and fun. Thus, Wordwall can be stated as an effective learning medium for developing English vocabulary, both in face-to-face learning and online learning.